Improvement of Modified Rotor on Aerodynamic Performance of Hybrid Vertical Axis Wind Turbine - Shaohua Chen; Chenguang Song; Zhong Qian; Aihua Wu; Yixian Zhu; Jianping Xia; Jian Wang; Yuan Yang; Xiang Chen; Yongfei Yuan; Chao Chen; Yang Cao (Energies, 2025)
In this paper, the aerodynamic performance of an improved hybrid vertical-axis wind turbine is investigated, and the performance of the hybrid turbine at high tip–speed ratios is significantly enhanced by adding a spoiler at the end of the inner rotor. The improved design increases the average torque coefficient by 7.4% and the peak power coefficient by 32.4%, which effectively solves the problem of power loss due to the negative torque of the inner rotor in the conventional hybrid turbine at high TSR; the spoiler improves the performance of the outer rotor in the wake region by optimizing the airflow distribution, reducing the counter-pressure differential, lowering the inner rotor drag and at the same time attenuating the wake turbulence intensity. The study verifies the validity of the design through 2D CFD simulation, and provides a new idea for the optimization of hybrid wind turbines, which is especially suitable for low wind speed and complex terrain environments, and is of great significance for the promotion of renewable energy technology development.